Forensic Investigation and Fraud Detection in Nigeria: Leveraging on Artificial Intelligence - Chukwuekwu Nordi Okonta; Chiamogu Anselm Nnamdi (CV. Proaksara Global Transeduka, 2025)
This study explores the integration of Artificial Intelligence (AI) in forensic investigations for fraud detection within Nigerian firms. As conventional approaches prove inadequate against increasingly complex fraudulent activities threatening business sustainability, the research examines how AI technologies can enhance investigative processes. Using a documentary approach, the study analyzes the application of data analytics, machine learning algorithms, and predictive modeling in improving the speed, accuracy, and efficiency of fraud detection. Despite implementation challenges in the Nigerian context, findings indicate that AI-driven forensic techniques facilitate more effective fraud detection and prevention through proactive monitoring. The study recommends that Nigerian firms prioritize integrating AI technologies into their forensic frameworks, provide regular training for forensic teams on AI tools, and collaborate with technology providers to develop customized solutions addressing specific fraud detection challenges within Nigerian businesses.